A CLUMPY STELLAR WIND AND LUMINOSITY-DEPENDENT CYCLOTRON LINE REVEALED BY THE FIRST SUZAKU OBSERVATION OF THE HIGH-MASS X-RAY BINARY 4U 1538-522 - Hemphill, Paul B.; Rothschild, Richard E.; Markowitz, Alex; Fuerst, Felix; Pottschmidt, Katja; Wilms, Jörn (Astrophysical Journal, 2014)
We present results from the first Suzaku observation of the high-mass X-ray binary 4U 1538-522. The broadband spectral coverage of Suzaku allows for a detailed spectral analysis, characterizing the cyclotron resonance scattering feature at 23.0 +/- 0.4 keV and the iron K alpha line at 6.426 +/- 0.008 keV, as well as placing limits on the strengths of the iron K beta line and the iron K edge. We track the evolution of the spectral parameters both in time and in luminosity, notably finding a significant positive correlation between cyclotron line energy and luminosity. A dip and spike in the light curve is shown to be associated with an order-of-magnitude increase in column density along the line of sight, as well as significant variation in the underlying continuum, implying the accretion of a overdense region of a clumpy stellar wind. We also present a phase-resolved analysis, with most spectral parameters of interest showing significant variation with phase. Notably, both the cyclotron line energy and the iron K alpha line intensity vary significantly with phase, with the iron line intensity significantly out of phase with the pulse profile. We discuss the implications of these findings in the context of recent work in the areas of accretion column physics and cyclotron resonance scattering feature formation.
Keywords: pulsars: individual (4U 1538-522); stars: magnetic field; stars: oscillations; X-rays: binaries; X-rays: stars